LKIAå¦æ ¡åˆä¸ä¸€å¹´çº§å¦ç”Ÿç¬”é¡ºåè¯¯åˆ†æžåŠæ•™å¦å¯¹ç– - SAFITRI, NUR (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The author conducted research on seventh-grade students at SMP LKIA Pontianak as the research subjects. This study aims to analyze the forms of errors in writing the stroke sequence "han" and the learning strategies. To achieve the research objectives, the author collected data using questionnaires and interviews. Based on the results obtained, the author concludes that errors in writing the stroke sequence are divided into "Errors Based on Stroke Position."In the process of learning Mandarin, some students still find writing hanzi very difficult, especially in writing the stroke sequence of hanzi. The factors that influence errors in writing the stroke sequence are: students have difficulty remembering the strokes of hanzi and often do not pay attention to the stroke sequence when writing hanzi, lack of focus during online learning, and the teaching methods.Based on the analysis results, the author provides several suggestions for learning the sequence of Mandarin strokes.